2016
DOI: 10.3892/ijo.2016.3708
|View full text |Cite|
|
Sign up to set email alerts
|

Expression and function of PIM kinases in osteosarcoma

Abstract: The provirus integrating site Moloney murine leukemia virus (PIM) family of serine/threonine protein kinases is composed of three members, PIM1, PIM2 and PIM3, which have been identified as oncoproteins in various malignancies. However, their role in osteosarcoma (OS) remains largely unknown. This study aimed to examine the expression patterns and the clinical significance of PIM kinases in human OS and their biological effects in human OS cell lines. Immunohistochemical staining was used to detect PIM kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Furthermore, patients with high PIM1 expression had a poorer OS compared with patients with low PIM1 expression. Our findings are similar to those of Shuai [72] , Guo [73] , and His [74] reporting different kinds of carcinomas, suggesting that PIM1 may act as a prognostic factor for PCNSL patients.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, patients with high PIM1 expression had a poorer OS compared with patients with low PIM1 expression. Our findings are similar to those of Shuai [72] , Guo [73] , and His [74] reporting different kinds of carcinomas, suggesting that PIM1 may act as a prognostic factor for PCNSL patients.…”
Section: Discussionsupporting
confidence: 89%
“…When we consider the link between transcriptional changes and sperm phenotypic effects, the higher expression levels of PIM1 appear to be consistent with our earlier findings of longer and faster swimming sperm in BY (Yang, Zhang, Wang, Yang, et al, 2020; Yang, Zhang, Wang, Zhang, et al, 2020). The relationship between the expression level of PIM1 and sperm trait variation has yet been explored, nonetheless, several studies have shown that PIM1 can accelerate cancer cell motility and the overexpression of PIM1 results in increased cancer cell motility (Mou et al, 2016; Santio et al, 2020; Tanaka et al, 2009). PIM1 kinase accelerates cell motility by phosphorylating and activating target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical significance of Pim-1 has not been widely recognized and is somewhat controversial in different tumors. Studies have shown that the expression of Pim-1 is negatively correlated with the prognosis of leukemia, 26 lymphoma, 27 head and neck tumors, 28 - 30 osteosarcoma, 31 - 33 gallbladder cancer, 34 colorectal cancer, 35 , 36 and non-small cell lung cancer (NSCLC). 37 Nevertheless, Reiser-Erkan et al 38 showed that Pim-1 kinase overexpression in pancreatic cancer had a good prognosis.…”
Section: Introductionmentioning
confidence: 99%